2019
DOI: 10.1002/cam4.2666
|View full text |Cite
|
Sign up to set email alerts
|

Role of alternative splicing signatures in the prognosis of glioblastoma

Abstract: Background Increasing evidence has validated the crucial role of alternative splicing (AS) in tumors. However, comprehensive investigations on the entirety of AS and their clinical value in glioblastoma (GBM) are lacking. Methods The AS profiles and clinical survival data related to GBM were obtained from The Cancer Genome Atlas database. Univariate and multivariate Cox regression analyses were performed to identify survival‐associated AS events. A risk score was calculated, and prognostic signatures were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 76 publications
(160 reference statements)
2
19
0
Order By: Relevance
“…Thereafter, we uncovered FBXL19 as the downstream target of miR-532-3p in glioma. Importantly, Xie et al [ 31 ] recognized FBXL19 as one of the core genes in glioblastoma. Our study found that FBXL19 was up-regulated in glioma cells, and down-regulating FBXL19 could restrict the growth and stemness of glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, we uncovered FBXL19 as the downstream target of miR-532-3p in glioma. Importantly, Xie et al [ 31 ] recognized FBXL19 as one of the core genes in glioblastoma. Our study found that FBXL19 was up-regulated in glioma cells, and down-regulating FBXL19 could restrict the growth and stemness of glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…The present study used bioinformatics techniques to identify survival-associated AS events in order to construct splicing signatures for the prediction of prognosis, orchestrate SF-AS networks and assess their potential underlying molecular mechanism. Previously, SpliceSeq analyses have been adopted to establish AS profiling and construct prognostic models in glioma; several potential AS events were identified in pan-glioma and GBM cohorts, including adenine DNA glycosylase, metalloreductase STEAP3, SUMO-conjugating enzyme UBC9, von Hippel-Lindau disease tumor suppressor, BTB/POZ domain-containing protein KCTD7, protein S100-A4, endothelin-converting enzyme 2 and lymphocyte antigen 6K (29)(30)(31). Additionally, several prognostic models based on AS events have been constructed for prognosis prediction, which may complement the molecular classification, further identify potential glioma subgroups and highlight SFs as an important mechanism of splicing regulation in the carcinogenesis and aggressiveness of GBM (9,31-33).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide transcriptome analysis in GBM has revealed the presence of aberrant AS events in tumors that generate tumorspecific isoforms having enhanced oncogenic activities as compared to normal brain. Such isoforms are also involved in therapy resistance [17][18][19][20]. For example, splicing profiles of glioma subtypes proneural (PN) and mesenchymal (MES) glioma stem cell (GSC) lines have shown significant differences in the genes implicated in the hallmark characteristics of cancer, contributing to PN-MES transition and subsequent tumor heterogeneity and resistance [21].…”
Section: Introductionmentioning
confidence: 99%